Synthesis of Some New Open-Chain Conjugated Azomethines and N-Aryl-1-Cyano-α-Methylcinnamylamines - Kaur, Jaspreet; Singh, Bldev; Krishan Singal, Kewal (Asian Journal of Chemistry, 2010)
The reactivity of carbon-nitrogen double bond lies in between that of carbon-oxygen and carbon-carbon double bond. Some new open-chain conjugated azomethines, i.e., α-methyl cinnamylideneanilines (3) have been prepared by condensation of a-methyl- cinnamaldehyde with a series of various substituted anilines. The addition of hydrocyanic acid to these openchain conjugated azomethines leads to some new amines identified as N-aryl-1-cyano-α- methylcinnamylamines (4). All the products have been identified by their spectral data. The addition of hydrocyanic acid occurs at carbon-nitrogen double bond rather than carboncarbon double bond of the azomethines indicating that the former is more reactive than the latter.